Letters concerning the present state of the French nation. Containing a comprehensive view of the political state, agriculture, trade and commerce, [...]. With a complete comparison between France and Great Britain [...]. [By A. Young] (Nicoll, 1769)
Facsimile reprint: Farnborough, Gregg International Publishers, 1969.